2021
DOI: 10.3390/foods10092017
|View full text |Cite
|
Sign up to set email alerts
|

Raw Cow Milk Protein Stability under Natural and Technological Conditions of Environment by Analysis of Variance

Abstract: Heat stability (HS) is substantial technology property of raw milk. Analysis of sources of HS variation and its regular monitoring can contribute to creating higher added value in the dairy industry. The goal of this analysis was to assess the practice sources of raw cow milk HS variability on the results of an extensive data set of bulk tank milk samples. There was implemented neither a compositional technology modification nor acidity adjustment of milk, just original raw milk was used for the analysis. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…The lactation stage (days in milk) influenced milk fermentation ability and SCS; non-fat solids influenced renneting. Hanuš et al [ 47 ] carried out, within three years, an analysis of 2634 raw milk samples. The thermostability was, on average, 18.8 min and was affected by all 12 evaluated factors, e.g., year, season, milk yield, breed, milking, and summer grazing.…”
Section: Resultsmentioning
confidence: 99%
“…The lactation stage (days in milk) influenced milk fermentation ability and SCS; non-fat solids influenced renneting. Hanuš et al [ 47 ] carried out, within three years, an analysis of 2634 raw milk samples. The thermostability was, on average, 18.8 min and was affected by all 12 evaluated factors, e.g., year, season, milk yield, breed, milking, and summer grazing.…”
Section: Resultsmentioning
confidence: 99%
“…Somatic cell count and TBC were reported to be both health and hygiene indicators for dairy cows (Hanuš et al, 2021). In discussing the difference between ethanol stable and unstable milk with SCC and TBC in this study, a significant increase in both SCC and TBC in the unstable milk was observed, as shown in table (1).…”
Section: Discussionmentioning
confidence: 51%
“…Also, the results of Oliveira et al (2013) suggested that the high SCC may be involved as a causal factor for the high incidence of ethanol unstable milk as the last showed higher SCC as well as lower casein contents which approved our results. Lately, Hanuš et al (2021) cleared that, milk stability values suggested similar seasonal dynamics with the SCC and TBC and opposed composition patterns to crude protein, fat, SNF, and TS content.…”
Section: Discussionmentioning
confidence: 95%
“…Such changes in forage chemical composition could affect either cows' feeding behaviour or the metabolism of carbohydrates and protein in the rumen. This could be the origin of the different native macro-and micro-compounds detected in the milk in winter compared to summer [47]. Moreover, evidence has been reported of a strong impact of raw milk's indigenous microbial community on the development of its VOC profile, but indoor milk is more likely to have higher proportions of host/gut-associated microbes [48].…”
Section: Milk Volatile Organic Compoundsmentioning
confidence: 99%